2002
DOI: 10.1614/0890-037x(2002)016[0401:groros]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Growth Response of Rice (Oryza sativa) and Red Rice (O. sativa) in a Replacement Series Study1

Abstract: A replacement series study was conducted in a greenhouse in 1998 and 1999 to evaluate the interference interactions among two rice cultivars and two red rice ecotypes. Plants were established in proportions of 3:0, 2:1, 1:2, and 0:3 (rice–red rice) plants/pot. Relative yield of Kaybonnet based on the shoot dry weight was lower than that of KatyRR or LA3, whereas PI 312777 was comparable to that of KatyRR and LA3. These results indicate that Kaybonnet was less competitive than PI 312777 when contrasted with Kat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
44
2
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 11 publications
6
44
2
3
Order By: Relevance
“…Determination of competitive interactions between crops and weeds requires appropriate experimental designs and methods of analysis, and the conventional replacement series experiments are the most used to clarify these relationships (Agostinetto et al, 2013;Cralle et al, 2003;Crotser & Witt, 2000;Estorninos et al, 2002;Roush et al, 1989;Vida et al, 2006). In these experiments, the crops generally achieve greater competitive ability than weeds.…”
Section: Introductionmentioning
confidence: 99%
“…Determination of competitive interactions between crops and weeds requires appropriate experimental designs and methods of analysis, and the conventional replacement series experiments are the most used to clarify these relationships (Agostinetto et al, 2013;Cralle et al, 2003;Crotser & Witt, 2000;Estorninos et al, 2002;Roush et al, 1989;Vida et al, 2006). In these experiments, the crops generally achieve greater competitive ability than weeds.…”
Section: Introductionmentioning
confidence: 99%
“…A interpretação dos dados de experimento substitutivo resulta em medida da competitividade entre as espécies, com base na resposta relativa da variável em estudo, podendo ser: a produção de massa seca da parte aé-rea, área foliar, estatura, afilhamento e índice de cobertura do solo; contudo, a resposta é dada pela variação da proporção de plantas associadas (Crotser & Witt, 2000;Estorninos Jr. et al, 2002;Cralle et al, 2003;Vida et al, 2006). Em experimentos conduzidos em séries substitutivas, geralmente as culturas demonstram maior habilidade competitiva do que as espécies daninhas; isso ocorre porque, em campo, o efeito da planta daninha sobre a cultura se deve, principalmente, ao nível de infestação e não à sua habilidade competitiva individual (Vilá et al, 2004).…”
Section: Introductionunclassified
“…These results are partly in agreement with the information available from the literature. Several studies pointed out that the effects of weedy rice interference on dynamics of different growth parameters of rice can vary from not significant to strong, according to the experimental conditions (Montealegre and Clavijo, 1991;Kwon et al, 1991a;Estorninos et al, 2000Estorninos et al, , 2002Eleftherohorinos et al, 2002). For instance, in this study a 5% of plant height reduction due to competition was recorded in Thaibonnet in 1997 only, while Kwon et al (1991a) reported a reduction of 4.3% in the cultivar Lemont and 6% in the cultivar Newbonnet, with an infestation of 10 plants m -2 .…”
Section: Discussionmentioning
confidence: 99%